Screening of Indole-3-Acetic Acid (IAA) Productions by Endophytic Fusarium oxysporum Isolated from Phyllanthus niruri - Abdul Raffi, Junaidi; Mohamad Hasnul, Bolhassan (Universiti Malaysia Sarawak (UNIMAS), 2017)
Ten newly isolated endophytic fungi from Phyllathus niruri Linn. were identified as Fusarium oxysporum. These isolates were screened out for their productivity of indole acetic acid (IAA) by the salkowski's method. Out of these isolates, two isolates showed high amount of indole acetic acid production, which were FO9 and FO10 with concentration of 23.52 μg/ml and 5.95 μg/ml, respectively.